Developing the Roles That Public Relations Play in Supporting 3R Activities by School Teachers in Johor - Amir A. Rahim, Shahrul; Nasir Markom, Mohd; Agil Alsagoff, Syed (International Journal of Engineering and Technology, 2018)
Public relations (PR) practitioners mainly assumes technical and managerial roles in organizations. However, this study reveals that in order to implement the Reduce, Reuse and Recycle (3R) activities, PR practitioners must possess close rapport with the teachers who will ultimately educate the target audiences. Occasionally, these dynamic relationships can derail PR practitioners from carrying out their actual role in promoting public relations. In-depth interviews were conducted at several designated schools to gain insights on how the relationships between PR practitioners and teachers can gauge the effectiveness such a campaign, besides identifying the major challenges in delivering relevant campaign messages. Results show that the relationship is an important element towards ensuring the PR practitioners’ success in developing the awareness campaign. These findings have implications in both the theory and practice of public relations, especially when considering the technician versus strategic manager’s role of public relations and the advancement of the field to support PR professionalism.